MORTALIN-Ca2+ axis drives innate rituximab resistance in diffuse large B-cell lymphoma. (1st July 2022) - Sun, Qi; Ye, Ying; Gui, Ailing; Sun, Xiaoting; Xie, Sisi; Zhan, Yuhang; Chen, Ruibo; Yan, Yichen; Gu, Juan; Qiu, Shi; Liu, Wen; Zuo, Ji; et al.
Abstract: Diffuse large B-cell lymphoma (DLBCL) is the most common subtype of non-Hodgkin's lymphoma, with the combination of rituximab and chemotherapy being the standard treatment for it. Although rituximab monotherapy has a remarkable response rate, drug resistance with unclear mechanisms and lack of effective second-line therapy limit the survival benefits of patients with lymphoma. Here, we report that MORTALIN is highly expressed and correlates with resistance to rituximab-based therapy and poor survival in patients with DLBCL. Mechanistically, gain- and loss-of-function experiments revealed that the voltage-dependent anion channel 1-binding protein, MORTALIN, regulated Ca 2+ release from the endoplasmic reticulum through mitochondria-associated membrane, facilitating AP1-mediated cell proliferation and YY-1-mediated downregulation of FAS in DLBCL cells. These dual mechanisms contribute to rituximab resistance. In mouse models, genetic depletion of MORTALIN markedly increased the antitumor activity of rituximab. We shed mechanistic light on MORTALIN-Ca 2+ -CaMKII-AP1-mediated proliferation and MORTALIN-Ca 2+ -CaMKII-inhibited death receptor in DLBCL, leading to rituximab resistance, and propose MORTALIN as a novel target for the treatment of DLBCL. Highlights: MORTALIN overexpression in DLBCL. MORTALIN correlates with rituximab resistance and poor survival. MORTALIN releases Ca 2+ from ER and triggers CaMKII autophosphorylation. Proliferation promotion and apoptosis inhibition confer rituximab resistance. Knockdown of MORTALIN in DLBCL reverses rituximab resistance.